Hubungan Dukungan Keluarga terhadap Kepatuhan Berobat Lansia Hipertensi Masa Pandemi Covid-19 di Prolanis UPTD Puskesmas Payangan - Ni Made Dwi Artini; Ni Kadek Muliawati; Ni Ketut Ayu Mirayanti (Jurnal Akademika Baiturrahim Jambi, 2022)
The elderly face a significant risk of contracting the corona virus disease, including with a decrease in physiological conditions, namely the elderly with hypertension. Elderly people with hypertension are expected to comply with treatment and have regular check-ups at health care facilities every month. The attention of the family starts from delivering treatment to health services, helping with medical expenses, reminding that taking medication has an impact on patient compliance to undergo treatment. Lack of family support for patients with hypertension can cause an increase in the number of people with hypertension, especially in the elderly. This study aims to determine the relationship between family support and adherence to treatment for hypertension in the elderly during the covid-19 pandemic. The research uses quantitative methods, with a correlation research design and a cross sectional approach. The sample of this study was the elderly with hypertension, using a purposive sampling technique, totaling 44 people. The results showed that most of the family support was in the good category, as many as 18 respondents (40.9%). Compliance with treatment is mostly in the high category, as many as 16 respondents (36.4%). It was concluded that there was a relationship between family support and adherence to treatment for hypertension in the elderly during the Covid-19 pandemic (p=0.000). It is recommended for nurses to routinely carry out health education about hypertension